FIQH STUDY OF GOLD PAWNING PRACTICES IN SHARIA PAWNSHOPS IN SUMBAWA DISTRICT FROM THE PERSPECTIVE OF ISLAMIC LAW - Eka Nurmayanti; Feri Irawan (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
In recent years, the public's need for financial services that are fast, safe, and in accordance with sharia principles has increased significantly. One form of service that is growing rapidly is gold pawning at Pegadaian Syariah. In Sumbawa Regency, this practice has become a financing alternative that is in high demand by the community due to its relatively easy process and the guarantee of conformity with Islamic values. However, although the Sharia Pawnshop has implemented contracts such as rahn (pawn) and ijarah (rental) in its operations, there are still a number of issues that require further study from the perspective of Islamic law. The main issues identified include limited public understanding of the sharia contracts used, lack of information disclosure regarding administrative costs, and the potential for shubhat in service delivery. This shows that the implementation of contracts is not only formal, but must also be reviewed from the aspects of justice, transparency, and freedom from elements of usury and gharar, as regulated in muamalah fiqh. This research was conducted to answer the need for a study that connects fiqh theory and actual practice in Islamic financial institutions at the regional level. Using a qualitative approach and descriptive-analytical method, this study aims to assess the suitability of gold pawning practices at Pegadaian Syariah Sumbawa Regency with the principles of Islamic law. The research also recommends strengthening Islamic financial literacy and increasing information transparency so that the service can run more optimally and be sharia-compliant